Forestry and its relationship other-than-human - Arce-Rojas, Rodrigo Severo (2023)
The purpose of this article is to establish the relationship between forestry and the other-than-human from the complexity approach, and to enrich the theoretical framework and practices of forestry by transcending the strictly anthropocentric perspective. From the review, reflection and analysis, it is found that the complexity sciences, by having a clearer orientation to the understanding of life in general, broaden the field of vision of forestry to recognition the intrinsic value of the other-than-human within forests. Although institutionally, National Forest and Wildlife Service (SERFOR) maintains the logic of forest resources with a productive orientation, in its structure provides a good framework for respecting the other-than-human of the forests. However, this logic does not guide the conception and practice of forestry professionals who, to a considerable extent, still maintain a strongly utilitarian and production-oriented perspective.